2017
DOI: 10.1111/micc.12344
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vascular caliber associated with cardiac and renal target organ damage in never‐treated hypertensive patients

Abstract: In never-treated HT patients, reduced CRAE and CRVE were associated with cardiac and renal preclinical damage, ie, left ventricular hypertrophy and albuminuria, but not estimated glomerular filtration rate or vascular stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 58 publications
1
13
1
Order By: Relevance
“…17 However, two of the three studies of hypertensive adult patients showed that narrower (usually considered to be better) retinal venular caliber was weakly associated with higher PWV (r = −0.06 to −0.22). 49,50 Notably, this finding was in the opposite direction to that expected. Of the four studies examining AVR, two European studies provided some evidence that lower (worse) AVRs were associated with higher PWV (in general population r = −0.18, P < 0.01 and in hypertensive patients r = −0.12, P = 0.08).…”
Section: Associations Of Retinal Microvascular Caliber With Functiocontrasting
confidence: 61%
See 4 more Smart Citations
“…17 However, two of the three studies of hypertensive adult patients showed that narrower (usually considered to be better) retinal venular caliber was weakly associated with higher PWV (r = −0.06 to −0.22). 49,50 Notably, this finding was in the opposite direction to that expected. Of the four studies examining AVR, two European studies provided some evidence that lower (worse) AVRs were associated with higher PWV (in general population r = −0.18, P < 0.01 and in hypertensive patients r = −0.12, P = 0.08).…”
Section: Associations Of Retinal Microvascular Caliber With Functiocontrasting
confidence: 61%
“…In children, there was little evidence that venular caliber was associated with PWV ( r = 0.04) . However, two of the three studies of hypertensive adult patients showed that narrower (usually considered to be better) retinal venular caliber was weakly associated with higher PWV ( r = −0.06 to −0.22) . Notably, this finding was in the opposite direction to that expected.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations